(untitled) (Revista Lusófona de Educação, 2026)
The study aims to review “AI for Educators: Learning Strategies, Teacher Efficiencies, and a Vision for an Artificial Intelligence Future” by Matt Miller, published in 2023. The book examines the nature of artificial intelligence and its potential applications in education in a global context marked by rapidly increasing interest in and concern about it. Structured into eight chapters, the book invites educators to adopt “the glasses of tomorrow” to prepare students for this new reality without either completely rejecting or uncritically embracing artificial intelligence. Keywords: Artificial intelligence; AI; Educators; Glasses of tomorrow; Potentials of AI.